Stabilization of Environmental Conditions when Liquid Density Measuring by Hydrostatic Weighting - N. V. Bakovets; K. V. Kozadayev (Приборы и методы измерений, 2024)
When assessing the quality of products, especially oil and oil products, the density value is widely used along with other parameters. Density data are fundamental for studying the properties of liquids, their identification and determining the degree of purity. They are also necessary for indirectly assessing with a certain degree of accuracy some other properties of the liquid, such as specific gravity, thermal expansion or contraction, the mass of a known volume of liquid, etc. In turn, the accuracy of the density determination determines the correctness of the decision made in the technological quality control of the manufactured products. Determining the density of a liquid with high accuracy requires maintaining stable temperature conditions during the measurement process. The purpose of the work was to establish the effect of temperature stability on the reproduction and transmission of the unit of liquid density. To stabilize the temperature, a technical solution is proposed, implemented in the form of a climatic chamber, inside which reference equipment is placed. A study of the temperature conditions in the process chamber was carried out. It was found that due to the technical solutions used, the influence of environmental conditions on the change in the temperature of the liquid under study is a negligible value.